Geospatial Technology Environmental and Social Applications - Imperatore, Pasquale; Pepe, Antonio (IntechOpen, 2016)
The pervasive relevance of geospatial information and the development of emerging geospatial technologies offer new opportunity for bridging the gap between remote sensing scientific know-how and end users of products and services. Geospatial technology comprises tools and techniques dealing with the use of spatially referenced information, for the description and modeling of spatial and dynamic phenomena related to the Earth's environment. This book addresses environmental and social applications of geospatial technologies, thus also providing a multidisciplinary perspective on emerging geospatial techniques and tools. It consists of ten chapters offering insight into geospatial technology progress and trends. Authors present several application-oriented studies from various parts of the world, including applications in collaborative geomatics, geospatial statistics, GIS, agriculture, and natural hazard monitoring.